Analyst Behavior: The Geography of Social Interaction. Issue 3 (2nd July 2016) - König, Frederik
ABSTRACT: In this paper, I provide empirical evidence that an analyst working in Germany is more likely to publish a high (low) price target regarding a DAX30 stock when other Germany based analysts are also optimistic (pessimistic) about the same stock. This effect of geographical proximity is not biased by the fact that DAX30 companies are headquartered in Germany. Shedding light on how influence takes place, I show that influence through communication and the exchange of opinion within small groups of analysts plays a vital role. This mainly applies during a bullish market environment. When markets are bearish, analysts' incentives induce them not to deviate too much from the overall average, such that then observational learning has a greater impact.